Dynamics and control policies analysis of semi-active suspension systems using a full-car model - Ihsan, Sany Izan; Faris, Waleed Fekry; Ahmadian, Mehdi (InderScience Publishes, 2007)
Several control policies of semi-active system, namely skyhook,groundhook and hybrid controls are presented. Their ride comfort, suspension displacement and road-holding performances are analysed and comparedwith passive systems. The analysis covers both transient and steady-state responses in time domain and transmissibility response in frequency domain.The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement for typical passenger cars. The hybrid control policy is also shown to be a better compromise between comfort, road-holding and suspension displacement than the skyhook and groundhook control policies.